Integrating Zero Trust Architecture and Attribute-Based Encryption for Secure Cloud-IoT Access Control: A Systematic Literature Review - Mutiara Sovina; Ivi Lazuly; Faisal Amir Harahap; Yusfrizal Yusfrizal; Surya Darma; Darma Indra Gultom (Yayasan Sinergi Multidimensi Kreatif, 2026)
The rapid adoption of cloud computing and the Internet of Things (IoT) has significantly increased the complexity of securing distributed computing environments. Conventional perimeter-based security mechanisms are no longer sufficient to protect dynamic systems that require continuous authentication, authorization, and data confidentiality. This study presents a Systematic Literature Review (SLR) that investigates the integration of Zero Trust Architecture (ZTA) and Attribute-Based Encryption (ABE) as an advanced access control approach for Cloud-IoT environments. The review follows the PRISMA methodology to identify, screen, evaluate, and synthesize recent studies related to secure access control, lightweight cryptographic mechanisms, dynamic trust management, and scalable deployment strategies. The findings indicate that combining ZTA with ABE provides stronger protection through continuous identity verification and fine-grained data access control. Several optimization techniques, including lightweight CP-ABE, outsourced decryption, decentralized key management, and context-aware trust evaluation, have demonstrated considerable improvements in security, computational efficiency, and scalability for resource-constrained IoT devices. Nevertheless, challenges remain in attribute revocation, key management complexity, real-time processing, interoperability, and post-quantum security. This review provides a comprehensive overview of current research trends, implementation challenges, and future research opportunities, serving as a valuable reference for researchers and practitioners developing secure and scalable Cloud-IoT access control frameworks.